Sustainable Logistics Through Waterways: Balancing Cost, Efficiency, and Environmental Impact - Ma'ruf; Zahra Aulia; Putri Aprilya Nurpratiwi; Muhammad Fikri Fadhilah; Dwi Sandinata Prayoga; Inez Arisa Daulay (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The use of various modes of transportation in transporting goods and passengers certainly presents each advantage. However, transporting logistics by land has various negative impacts such as pollution, congestion, and excessive dependence on land transportation [19]. The use of land transportation modes also has an impact on the high cost per kilometer with the same distance traveled. The use of inland waterways as a mode of logistics transportation has increased in recent years especially in Europe and Asia, of course this is driven by the benefits offered. The main objective of this study is to analyze and compare the effectiveness of sustainable logistics using inland waterway modes, especially in the context of cost, operational efficiency, and environmental impact. This research aims to provide an in-depth insight into the potential benefits and challenges faced in implementing an inland waterway-based logistics system. The method used to find data and information is to use the literature study method that discusses the use of inland waterways. From the results of the studies collected and analyzed, it was found that Inland Waterway has many positive impacts and greater benefits when compared to using other transportation routes. In addition, the application of Inland Waterway has succeeded in reducing air pollution levels, reducing shipping costs, and as the most environmentally friendly branch of water transportation.